Sex Determination in Forensic Dentistry: Insights from Dental Resilience and Artificial Intelligence (Bulletin of the International Association for Paleodontology, 2024)
This literature review investigates the potential enhancement of sex determination accuracy in forensic dentistry through the application of artificial intelligence (AI) techniques. A meticulous search of the literature has been conducted, focusing on the utilization of AI for sex determination based on dental attributes. A prominent study highlighted in this review primarily examines the implementation of algorithms like the Multilayer Perceptron (MLP), Naive Bayes, and decision trees, specifically for discerning tooth characteristics linked to sex determination. Compared to its counterparts, the MLP algorithm emerged as the most effective, demonstrating the highest accuracy and minimal error margin. Furthermore, the integration of AI in DNA tracing using dentine and pulp samples exhibited commendable accuracy in determining sex within dental specimens. Of particular significance are canine teeth, which play a pivotal role in sex determination due to their robust physical attributes encompassing size, strength, and resistance against degeneration and periodontal issues. Dental structures provide a reliable source for DNA analysis, with AI models effectively discerning sexual dimorphism within canine dental formations. The impressive efficacy of AI methodologies, notably exemplified by the MLP algorithm, significantly surpasses conventional techniques, establishing an outstanding accuracy rate of 84%.Keywords: artificial intelligence, forensic dentistry, legal identity, sex determination